Propriozeption des Schultergelenks bei jungen Tennisspielern - Jerosch, J.; Thorwesten, L.; Teigelkotter, T. (Sportverletzung Sportschaden, 1997)
In 60 adolescent volunteers aged 8 to 16 years we assessed the proprioceptive capability of the shoulder complex by an angle reproduction test. The purpose of the study was to evaluate the proprioceptive capability of adolescent tennis players. 40 were tennis players, 20 non tennis players served as a control group. Documentation of the reproduced angle was performed by a motion analyzing system with passive markers. Angle reproduction of all volunteers was best in the midrange of motion (100 degrees flexion, 100 degrees abduction, neutral rotation in 90 degrees abduction). The worst results were documented below shoulder level (50 degrees flexion, 50 degrees abduction, internal rotation in 90 degrees abduction). A correlation to sex or dominant extremity could not be found. Subjects older than 12 years showed a tendency for better angle reproduction compared to the younger subjects. Tennis players older than 12 years demonstrated significant better capabilities for angle reproduction in some movements of the shoulder complex.